Assessing young adult consumers’ responses to green personal care products: insights from extended theory of planned behavior - Zainudin, Norzalina; Law, Kai Wei; Osman, Syuhaily; Munusami, Chandramalar (Human Resource Management Academic Research Society, 2022)
The purpose of this study is to examine the role of intention and other predictors in predicting consumers’ behaviour of purchasing green personal care products. This was a cross sectional study with 305 college students in the 2020-2021 academic year in completed a self-reported online survey. The findings revealed that three predictors as attitude, subjective norm, and perceived behavioral control have a significantly positive influence on green purchase intention of green personal care products among students. The analysis also showed that the additional of environmental concern and price to the standard TPB model has contributed to the increase in variance for the model. However, analysis of the mediation effect of intention for perceived behavioral control and behavior also shows insignificant. To academics, our findings indicate that future intervention should consider TPB constructs and additional constructs, price, and environmental concerns. It also provides insight to the green marketer in understanding young consumers' decision-making in relation to green personal care products. These findings can assist marketers in starting point for the conception of target group-specific strategies. This study offers valuable insight into current academic findings on young adult consumers and climate-friendly products research which further enhance the predicting of the TPB model.